Using crop intercepted solar radiation and vegetation index to estimate dry matter yield of Choy Sum - He, Yiyin; Wang, Zhao; Sun, Sashuang; Zhu, Lijun; Li, Yu; Wang, Xiaoxiao; Shi, Jiang; Chen, Si; Qi, Dunchang; Peng, Junxiang; Zhou, Zhenjiang (Frontiers in Plant Science, 2023)
An accurate assessment of vegetable yield is essential for agricultural production and management.One approach to estimate yield with remote sensing is via vegetation indices, which are selected in a statistical and empirical approach, rather than a mechanistic way. This study aimed to estimate the dry matter of Choy Sum by both causality guided intercepted radiation-based model and spectral reflectance-based model and compare their performance. Besides, the effect of nitrogen (N) rates on radiation use efficiency (RUE) of Choy Sum was also evaluated. A two-year field experiment was conducted with different N rate treatments (0, 25, 50, 100, 150, and 200 kg ha -1 ). At different growth stages, canopy spectra, photosynthetic active radiation, and canopy coverage were measured by RapidScan CS-45, light quantum sensor, and camera, respectively. The results reveal that exponential models best match the connection between dry matter and vegetation indices, with coefficients of determination (R 2 ) all of 0.74, 0.76, 0.75 and 0.76below 0.80 for normalized difference red edge (NDRE), normalized difference vegetation index (NDVI), red edge ratio vegetation index (RERVI) and ratio vegetation index (RVI), respectively. In contrast, accumulated intercepted photosynthetic active radiation (Aipar) showed a significant linear correlation with the dry matter of Choy Sum, with root mean square error (RMSE) of 9.4 and R 2 values of 0.82, implying that the Aipar-based estimation model performed better than that of spectral-based ones. Besides, the RUE of Choy Sum was significantly affected by the N rate, with 100 kg N/ha, 150 kg N/ha, and 200 kg N/ha having the highest RUE values. The study demonstrated the potential of Aipar-based models for precisely Estimate Dry Matter Yield 2 estimating the dry matter yield of vegetable crops, and understanding the effect of N application on dry matter accumulation of Choy Sum.